Application of essential oils in food industry: challenges and innovation. Issue 2 (4th March 2022) - Saeed, Kanza; Pasha, Imran; Jahangir Chughtai, Muhammad Farhan; Ali, Zaryab; Bukhari, Hina; Zuhair, Muhammad
ABSTRACT: Essential oils are highly volatile lipophilic mixture of plant secondary metabolites. Due to their diverse bioactive profiles, essential oils have strong antimicrobial and antioxidant properties, making them as an ideal replacement of synthetic food additives in commercial food products. In current scenario, packaged food consumerism posed real scourge of food-borne illnesses due to synthetic additives used to maintain organoleptic and microbiological food quality. Utilizing preservative properties of essential oils is considered as a natural solution to these problems. Essential oils not only enhance the product shelf life but also act as natural flavoring agent. Essential oil alone and in combination are also incorporated in food packaging material in order to control food-spoiling agents. This review is primarily focused to develop an insight on the novel applications of essential oil in commercial food production. GRAPHICAL ABSTRACT: uf0001